Occurrence and distribution of microplastics in surface water and sediments in China's inland water systems: A critical review. (10th January 2022) - Fan, Jianxin; Zou, Lan; Duan, Ting; Qin, Liang; Qi, Zenglin; Jiaoxia Sun
Abstract: Microplastics, as a new type of pollutant, have attracted wide attention due to their direct or potential effects on the environment and ecosystem. The input of inland rivers is an important source of microplastics in the ocean. In this review, pollution characteristics of microplastics in China's inland water systems were summarized, including their abundance, distribution, source, and key factors for microplastics pollution level. The abundance of microplastics presented spatiotemporal heterogeneity in the freshwater environment of China, and shapes of microplastics were mainly fibers and fragments, which were mainly transparent and colored, and the polymer types were mainly polypropylene (PP）and polyethylene (PE). Secondary microplastics were dominant in freshwater bodies, and the abundance of microplastics was usually related to the level of urbanization nearby. Microplastics in major drainage basins should be investigated to establish and calibrate accurate models for the assessment of microplastic migration mechanism and explore possible pathways of microplastics from terrestrial sources to inland water bodies. Sampling and pretreated methods take important role in accurate determination of microplastics, thus standardized analysis methods should be improved. Meanwhile, human activities are the key factors affecting microplastic pollution, related laws and regulations should be established and implemented effectively. This study reveals the contamination and characteristics of microplastics in the China's inland water bodies and supplies important data for further research on microplastics in fresh water. Highlights: Microplastics occur ubiquitous in several inland water systems in China. The abundance of microplastics presents spatiotemporal heterogeneity. The fibers and fragments were dominant, and PP and PE were polymer types. Morphological characteristics indicate microplastics originate mainly from secondary sources. Priorities for microplastic research in future are proposed.